The association between objectively-measured sedentary behavior patterns and predicted 10-year ASCVD risk - Zhisheng Liu; Pan Peng (Scientific Reports, 2024)
Abstract This study aims to investigated the association between sedentary behavior (SB) and predicted 10-year atherosclerotic cardiovascular disease (ASCVD) risk and determine whether the associations differ by how the behavior is accumulated, in US middle-aged and older adults. Cross-sectional data were derived from national health and nutrition examination survey (NHANES) 2003–2006. Seven-day wearing of accelerometer was used to assess SB pattern, exported as total SB, bouts of 1–9, 10–29, 30–59 and ≥ 60 min SB. Predicted 10-year ASCVD risk was calculated using validated pooled cohort equations. Linear regression was used to estimate adjusted coefficients. A total of 2327 participants were enrolled with mean age of 56.9 and mean predicted 10-year ASCVD risk of 10.7%. We observed significant associations of total SB and its longer accumulated patterns with higher 10-year predicted ASCVD risk, in a linear fashion and independent of a list of covariates. A 30 min increment per day of total SB, bouts in 10–29, bouts in 30–59 and bouts in ≥ 60 min were associated with 0.14, 0.14, 0.23 and 0.12% higher multivariable-adjusted 10-year predicted ASCVD risk. There are significant associations of total SB as well as its longer accumulated patterns with higher 10-year predicted ASCVD risk, independent of a list of covariates and in a linear fashion. The result indicates that reducing total sedentary time and interrupting long duration of prolonged SB, could be meaningful to for public guideline to lessen the personal and public health burden of cardiovascular health.